Handbook of nursing diagnosis - Carpenito-Moyet, Lynda Juall (Wolters Kluwer/Lippincott Williams & Wilkins Health, 2013)
" The ideal quick reference, this handbook offers practical guidance on nursing diagnoses and associated care. Sections cover Nursing Diagnoses, Health Promotion/Wellness Nursing Diagnoses, and Diagnostic Clusters--medical conditions with relevant collaborative problems and nursing diagnoses. The newest nursing diagnoses approved by NANDA International for 2012-2014 are included"--